Laws for a nation and laws for transnational commerce / John Thomas. - Thomas, John (Arbitrator at 24 Lincoln's Inn Fields) (The Hamlyn Lectures., 2025)
In the 75th Hamlyn Lectures, former Lord Chief Justice of England and Wales Lord Thomas examines Welsh law and the law used for transnational commerce to assess what laws are best national in their application and which are best transnational. He first argues that Wales as a nation should be able to make its own laws on the basis of clear principles and sets out possible solutions to the issues raised by the devolution of law-making powers in 1999. He then explains the success of English commercial law in attaining transnational use and examines the emergence of transnational law from the late nineteenth century. At a time of unprecedented change and competition, his analysis of the present position of the use of English law for transnational commerce and the challenges it faces provides the essential context for a series of practical options for its continued use in the future.